Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Pemoderasi - Delvinia Regina Tania, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to reexamine the effect of profitability and leverage on firm value and to determine the role of Corporate Social Responsibility (CSR) as a moderating variable in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. This study took 50 samples of manufacturing companies using the Purposive Sampling method. This study uses E-Views 9.0 software to process data. The results of the study show that profitability has a negative and not significant effect on firm value, leverage has a negative and not significant effect on firm value, Corporate Social Responsibility (CSR) has a negative and not significant effect on firm value, Corporate Social Responsibility (CSR) weakens the effect of profitability on firm value, and also weakens the effect of leverage on firm value.